HISTOGRAM EQUALIZATION BASED IMAGE ENHANCEMENT FOR MEDICAL IMAGE PROCESSING - M, Lavanya; T, Sivasakthi; U , Palani (International Journal of Psychosocial Rehabilitation, 2020)
In the medical field, resonance imaging (MRI) is one of the advanced techniques, which can be used to provide rich data regarding the human body. Tomography of the medical image may be a useful tool to help physicians to diagnose. Bar chart exploits are among the required steps within the image sweetening methods for Medical images. There are different ways of image sweetening, every one of them is required for a special sort of analysis. In this paper, Brightness preserving Dynamic Histogram Equalization (BPDHE) used for image enhancement. Contrast-enhanced is that the digital manipulating dispensed to increase excellence and reduces the noise in digital imaging.